Papuan Women and Their Culture: Reception Analysis of Cultural Identity Portrayed in "Noken Rahim Kedua" Documentary - Amanda Putri Nahumury; Y. Argo Twikromo (Rekam, 2025)
This study aims to identify the meaning of Papuan cultural identity in Noken Rahim Kedua documentary perceived by Papuan women. Employing the phenomenological method and Stuart Hall's encoding-decoding theory, this research explores the encoding process by filmmakers and the decoding process by Papuan women through in-depth interviews. Overall, the four Papuan women are in a negotiating reading. They did not simply accept the meaning constructed by the filmmaker. Lacking women's involvement in the documentary, led them to perceive that the film does not fully represent the voice of Papuan women.  Several dominant factors that influence the reception, including 1) Ethnic origin and cultural knowledge; 2) Family background; and 3) Surroundings or the environment. Regarding the values believed by the Papuan women, two significant findings emerged. First, all Papuan women viewers believed that gender equality is fundamental; however, one participant disagreed with the notion that men should not work.  Second, all participants, the Papuan women, believed that culture should be preserved, and they are proud of it because it is an identity marker. However, one of the participants stated that culture does not need to be maintained if it is considered burdensome or disadvantageous. Future researchers are encouraged to explore ethnic diversity, and for future documentary filmmakers, multiple perspectives of Papuan identity must be incorporated.